The periaqueductal grey area and the cardiovascular system. - Green, A; Wang, S; Owen, S; Aziz, T (2007)
In this chapter, we report that blood pressure can be increased or decreased depending on whether an electrode is in ventral or dorsal PAG. We also describe that it is theoretically possible to treat orthostatic hypotension. These are exciting developments not only because they provide an example of direct translational research from animal research to humans but also because they highlight a potential for future clinical therapies. The control of essential hypertension without drugs is attractive because of the side effects of medication such as precipitation of heart failure [10]. Similarly, drug treatment of orthostatic hypotension cannot differentiate between the supine and standing positions and can therefore lead to nocturnal hypertension [22, 29]. A stimulator could be turned off at night or contain a mercury switch that reacts to posture.